Peran persepsi terhadap electronic service quality dan electronic word-of mouth (e-wom) terhadap intensi pembelian ulang melalui e-commerce - Dian Febriany Putri; Sumaryono Sumaryono (University of Muhammadiyah Malang, 2021)
Expanding the process of buying and selling goods or business transactions from offline to online becomes a challenge for its users. The intensity of purchasing goods by consumers through e-commerce is influenced by various factors, one of which is the perception of electronic service quality and electronic word-of-mouth (e-wom). The purpose of this study is to find out the role of perceptions of electronic service quality and electronic word-of-mouth (e-WOM) toward re-purchase intention through e-commerce. Respondents in this research were individuals with an age range of 18-35 years and the total of respondents were 232 people. The sampling technique used purposive sampling. Data was collected using the re purchase intention, perception of electronic service quality, and e-WOM scales. Methods of data analysis using Structural Equation Modeling (SEM). The results of the study explain that one’s perception of electronic service quality and information circulating through e-WOM each have a role in influencing or strengthening consumer intentions to repurchase products through e-commerce.